Nutritional needs for exercise in the heat - Burke, L. M. (Comparative Biochemistry and Physiology Part A: Molecular & Integrative Physiology, 2001)
Although hot conditions are not typically conducive to optimal sports performance, nutritional strategies play an important role in assisting an athlete to perform as well as possible in a hot environment. A key issue is the prevention of hypohydration during an exercise session. Fluid intake strategies should be undertaken in a cyclical sequence: hydrate well prior to the workout, drink as much as is comfortable and practical during the session, and rehydrate aggressively afterwards in preparation for future exercise bouts. There is some interest in hyperhydration strategies, such as hyperhydration with glycerol, to prepare the athlete for a situation where there is little opportunity for fluid intake to match large sweat losses. Recovery of significant fluid losses after exercise is assisted by the simultaneous replacement of electrolyte losses. Carbohydrate (CHO) requirements for exercise are increased in the heat, due to a shift in substrate utilization towards CHO oxidation. Daily food patterns should focus on replacing glycogen stores after exercise, and competition strategies should include activities to enhance CHO availability, such as CHO loading for endurance events, pre-event CHO intake, and intake of sports drinks in events lasting longer than 60 min. Although CHO ingestion may not enhance the performance of all events undertaken in hot weather, there are no disadvantages to the consumption of beverages containing 4-8% CHO and electrolytes. In fact, the palatability of these drinks may enhance the voluntary intake of fluid. Although there is some evidence of increased protein catabolism and cellular damage due to production of oxygen radicals during exercise in the heat, there is insufficient evidence to make specific dietary recommendations to account for these issues.